THE ERGONOMICS PROBLEM IN TROTOIR CONSTRUCTION - Sutjana, I Dewa Putu (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Trotoir construction has become as one of the priorities of development in every town inBali Province; it is in accordance with the evaluation criteria of successful town development.The functions of trotoir are to provide comfortable and safety path for pedestrians and toprevent the traffic jam. But, unfortunately it has not yet met to the purpose. In relation to theproblem the study had been done to the trotoir condition along the street in Denpasar town. Theresults sowed that in general the trotoir (old and new construction) are not flat, too height, notcontinued, blocked by tree, traffic light pole, or holy building etc. These conditions produceunsafety and uncomfortable for the pedestrians especially to the elderly, handicapped (eye orleg) persons, wheel chair, baby trolley. In some trotoirs the accidents had been happened.Therefore, it is suggested that the trotoir must be constructed flatly, continued, not too height,synchronized with drainage system, street construction, electricity and telephone net work, andtree plantation for the green peace program.
Keywords: Trotoir, safety and comfortable pedestrian